2010
DOI: 10.1038/ajg.2010.275
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nonalcoholic Fatty Liver Disease on Insulin Resistance in Relation to HbA1c Levels in Nondiabetic Subjects

Abstract: A cross-sectional analysis was conducted in healthy, nondiabetic Korean adults to assess the prevalence of nonalcoholic fatty liver disease (NAFLD), to compare the prevalence of NAFLD across different glycemic ranges as assessed by glycosylated hemoglobin (HbA1c), and to examine the impact of NAFLD on insulin resistance in relation to HbA1c levels. METHODS:After rigorous exclusion criteria, the fi nal number of subjects who participated in a comprehensive health status checkup program was 99,969. All subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
79
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 34 publications
10
79
2
4
Order By: Relevance
“…These results indicate that improvement of hepatic steatosis is associated with improvement of glycemic control in relation to insulin resistance. Hepatic steatosis is well known to be closely associated with insulin resistance, which plays an integral role in the pathogenesis of type 2 diabetes (2,3,35). Despite this close association of hepatic steatosis with insulin resistance, a causal relationship between NAFLD and glucose metabolism has not been clearly established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that improvement of hepatic steatosis is associated with improvement of glycemic control in relation to insulin resistance. Hepatic steatosis is well known to be closely associated with insulin resistance, which plays an integral role in the pathogenesis of type 2 diabetes (2,3,35). Despite this close association of hepatic steatosis with insulin resistance, a causal relationship between NAFLD and glucose metabolism has not been clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…resistance (2,3). Recent study results have shown that NAFLD independently increases one's risk of diabetes and cardiovascular diseases (4)(5)(6)(7)(8), which suggests that treatment of fatty liver might ameliorate the risk of type 2 diabetes and cardiovascular diseases.…”
mentioning
confidence: 99%
“…On the multivariate analysis, age, sex, BMI, IFG, family history of diabetes, DL, HT, and physical exercise were adjusted as potential confounders between NAFLD and T2DM. Stratified analysis by sex was conducted because NAFLD is more prevalent in men than in women (22)(23)(24)(25)(26), and its pathogenesis has a sex-related difference (22,26).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that NAFLD is strongly associated not only with impaired glucose metabolism and obesity [5][6][7] but also with an increased risk to develop diabetes mellitus [8][9][10], and an independent association between NAFLD and glycated hemoglobin (HbA1c) levels has been reported in several studies [11][12][13][14]. HbA1c is the gold standard for evaluating glucose control in patients affected by diabetes mellitus and for monitoring the efficacy of therapies [15,16].…”
Section: Introductionmentioning
confidence: 99%